The Influence of Facilities, Price, Service Quality, and Food Menu Innovation on Customer Satisfaction at Paini Banjir Restaurant - Tasya Dwi Andini; Novrihan Leily Nasution; Praida Hansyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This research aims to determine and analyze the influence of facilities, price, service quality and menu innovation on customer satisfaction with equipment at the Paini Banjir Restaurant. The search method used is a quantitative method. The research population came from Paii Restaurant consumers. The sample used in this study was up to 100 people, obtained by an unintentional sampling method. Data collection was carried out by distributing questionnaires. The data analysis technique uses linear regression analysis using several SPSS software. The research results show that all research variables have an influence on customer satisfaction simultaneously, this can be seen from the calculated t value of all variables being greater than the t table value (1.984) with a significant value below 0.05, simultaneously the independent variables have an influence on the dependent variable. This can be seen from testing all calculated f values > f table, and the determination value of the research variables is 0.807 or 80.07% of the variables have an influence on consumer satisfaction.